Separable Hyperstructure and Delayed Link Binding - Brailsford, David F. (ACM, 1999)
As the amount of material on the World Wide Web continues to grow, users are discovering that the Web's embedded, hard-coded, links are difficult to maintain and update. Hyperlinks need a degree of abstraction in the way they are specified together with a sound underlying document structure and the property of separability from the documents they are linking. The case is made by studying the advantages of program/data separation in computer system architectures and also by re-examining some selected hypermedia systems that have already implemented separability. The prospects for introducing more abstract links into future versions of HTML and PDF, via emerging standards such as XPath, XPointer XLink and URN, are briefly discussed.